ШАҢАРАҚ - СУИЦИДИАЛ ҲӘРЕКЕТЛЕРДИ САПЛАСТЫРЫЎ ФАКТОРЫ СЫПАТЫНДА - Сулетбаева, Э. (ILIM hám JÁMIYET, 2017)
The article deals with the bad relations in families between parents and teenagers which can be the reasons of origin of suicidal state among teenagers and also there is given information about prevention of suicidal behavior among teenagers. Parents must spend more time with their children and be attentive, they should support and prevent the state of stress in time.